Applicability of Salting-out Liquid-liquid Extraction for New Fluorimetric Quantification of Omadacycline in Pharmaceutical Formulations and Biological Samples - Alzahrani, Eman; Abdel-Lateef, Mohamed A.; Salman, Baher I. (Current Pharmaceutical Analysis, 2024)
Objectives A detectable innovative fluorimetric method was used to determine omadacycline (OMC) in human plasma matrices, pharmaceutical tablets, and vials with high recovery rates and without biological interference. Methods The fluorimetric technique was used based on the interaction between 4-chloro7-nitrobenzofurazan (NBD-Cl) with a (2-ry amine group) in OMC at pH 8.0, which generates a fluorescent compound measured at 530 nm (exci 470 nm) following a 10-minute heating step at 80°C. The plasma and milk samples were treated with ammonium sulfate as a salting-out procedure. Results Omadacycline (OMC) was successfully determined in pharmaceuticals, plasma, and milk samples with a linear range from 60.0 to 700.0 ng mL-1, with the lower limit of detection (LOD 5.18 ng mL-1) and limit of quantitation (LOQ 15.72 ng mL-1). Conclusion This simple, reliable, and detectable fluorimetric method was successfully developed to determine omadacycline in pharmaceutical tablets, plasma samples, and milk with high recovery rates.
Keywords: human plasma analysis